Factors influencing graft potency in patients who underwent CABG for treatment of CAD - Vavlukis, M; Georgievska-Ismail L; Borozanov, V (My University, 2006)
Objectives: To identify factors that influence graft disease and native coronary arteries progression disease and prognostic implication of this process. Background: Unsolved problem in CABG patients is progression of the disease in bypass grafts and native coronary arteries. Methods: Data from 102 patients with CABG, who underwent re-coronarography, were analyzed: - Pre and post-operative variables: risk factors, clinical status, functional capacity, left ventricular parameters and angiographic status (before and after CABG). Proportional hazard regression model, was used, p<0.05 was considered statistically significant. Results: Cardiac death, myocardial infarction and heart failure were more frequent in patients with graft occlusion, non-stable angina pectoris in non-occlusive graft disease, which together with acute myocardial infarction was more often in patients with native coronary arteries progression disease. PCI was significantly more often performed on native coronary arteries. Conclusion: Graft disease and native coronary artery progression disease is a continuous process which can be slowed by aggressive risk factors reduction, medications, and PCI procedures. In contrary, it leads to unfavorable clinical outcome (Tab. 8, Fig. 6, Ref 19).